2011
DOI: 10.3324/haematol.2011.056010
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography/computed tomography surveillance in patients with Hodgkin lymphoma in first remission has a low positive predictive value and high costs

Abstract: BackgroundThe value of performing post-therapy routine surveillance imaging in patients with Hodgkin lymphoma is controversial. This study evaluates the utility of positron emission tomography/computed tomography using 2-[18F]fluoro-2-deoxyglucose for this purpose and in situations with suspected lymphoma relapse. Design and MethodsWe conducted a multicenter retrospective study. Patients with newly diagnosed Hodgkin lymphoma achieving at least a partial remission on first-line therapy were eligible if they rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
74
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 25 publications
(35 reference statements)
1
74
1
Order By: Relevance
“…However, both studies had a major (12)(13)(14)(15). Posttreatment and follow-up 18 F-FDG PET/CT studies have a strikingly high number of false-positive results, as has been reported for several lymphoma subtypes (16)(17)(18)(19), including Hodgkin lymphoma (20). Consequently, the studies by Gallamini et al (12,13) are methodologically seriously biased.…”
Section: Replymentioning
confidence: 83%
“…However, both studies had a major (12)(13)(14)(15). Posttreatment and follow-up 18 F-FDG PET/CT studies have a strikingly high number of false-positive results, as has been reported for several lymphoma subtypes (16)(17)(18)(19), including Hodgkin lymphoma (20). Consequently, the studies by Gallamini et al (12,13) are methodologically seriously biased.…”
Section: Replymentioning
confidence: 83%
“…Likewise, recent research is providing a growing body of evidence of the limitations in PET-CT usage in follow-up. For instance, a substantial number of false-positive PET-CT results was revealed in routine surveillance among patients who had achieved remission after first-line therapy, which is particularly unfortunate considering the high costs involved [21]. Maeda et al also reported that PET-CT has low positive predictive value in surveillance [22].…”
Section: Discussionmentioning
confidence: 99%
“…7 Even with its relatively high sensitivity, the risks and benefits of routine surveillance PET/CT imaging remain controversial, mainly, because of its cost, radiation burden and the high rate of false-positive results (30-80%) 3,[8][9][10][11][12] with potential consequences of overtreatment. In this issue of the Journal, El-Galaly et al report the value of surveillance PET/CT in a retrospective cohort of 161 HL patients who achieved a complete or partial remission after first-line treatment.…”
mentioning
confidence: 99%
“…In this issue of the Journal, El-Galaly et al report the value of surveillance PET/CT in a retrospective cohort of 161 HL patients who achieved a complete or partial remission after first-line treatment. 12 During a median follow-up of 34 months 14% of patients experienced a relapse. With an average of 1.9 PET/CT per patient, the positive predictive value (PPV) of routine PET/CT and clinically indicated PET/CT was 22% and 37%, respectively (P=0.02).…”
mentioning
confidence: 99%
See 1 more Smart Citation